Hydroxychloroquine as a Preventive and Therapeutic Option in Preeclampsia – a Literature Review - Deharde, Daniela; Klockenbusch, Walter; Schmitz, Ralf; Brand, Marcus; Köster, Helen Ann; Oelmeier de Murcia, Kathrin (Geburtshilfe und Frauenheilkunde, 2020)
Preeclampsia is one of the most feared complications of pregnancy and puerperium and represents a serious threat to mother and child. In addition, a history of preeclampsia increases the risk of future cardiovascular events. New diagnostic and therapeutic approaches are needed. New therapeutic options are currently being discussed, one of which is the administration of hydroxychloroquine. It is an antimalarial drug which is also used to treat rheumatological disease and its use in pregnancy is considered safe. A reduced incidence of preeclampsia in patients with selected rheumatological disorders after administration of hydroxychloroquine has already been shown; however, the case numbers are very low. Neither the full pathogenesis of preeclampsia nor the exact modes of action of hydroxychloroquine have been completely elucidated, but there are several common features which make hydroxychloroquine a promising option for the prevention and treatment of preeclampsia. Further research, especially prospective, randomized controlled trials, is needed to prove its efficacy. This review discusses the pathogenesis of preeclampsia and gives an overview of new options for its prevention and treatment, including the administration of hydroxychloroquine in pregnancy.
Keywords: hydroxychloroquine; rheumatological disease; preeclampsia